EFISIENSI JALUR PENGIRIMAN KURIR PAKET DENGAN MENGGUNAKAN ALGORITMA ANT COLONY OPTIMIZATION - Fitra Rahman, Rizki; Sucipto , Hadi; Mufarrihah , Iftitaahul; Ali , Mahrus (Inovate, 2025)
This research explores the use of Ant Colony Optimization (ACO) algorithm to optimize package delivery routes in the courier industry. With the increasing popularity of online shopping, delivery efficiency is becoming increasingly crucial. The ACO algorithm was chosen for its ability to solve the Traveling Salesman Problem (TSP) by finding the shortest route connecting multiple points. The research data was collected through interviews with couriers and analysis of the delivery route, which includes the coordinates of the package recipient to calculate the distance between points using MapBox. The results showed that the ACO algorithm was able to generate routes with shorter total distances compared to conventional methods. However, implementation in the field requires consideration of other factors such as the availability of package recipients, delivery demand at certain hours, and variations in delivery locations. This finding underscores the importance of considering various additional factors for the effective implementation of this method. The implementation of a web-based system that records the coordinates of the recipient and suggests efficient paths is proposed to improve delivery efficiency. Keywords: Ant Colony Optimization, Package delivery route, Traveling Salesman Problem